Economic governance between present requirements and future aspirations - Chine, Noual; Al-Sayed Abou Souliman, Mohamad Abdel Monem; Chine, Fairouz; Chine, Saida; Mohamed, Trifa (The International tax journal, 2025)
Governance in general, and economic governance in particular, are among the fundamental pillars for achieving the Sustainable Development Goals (SDGs), serving as the foundational structure that enhances the attainment of these objectives. Consequently, governance has garnered significant interest worldwide. Governments, policymakers, and regulatory bodies have dedicated considerable effort and substantial resources to developing legislation, policies, and applications related to governance and its implementation. Therefore, good governance is considered a key pillar for achieving the SDGs, as these goals call for “effective, transparent and accountable institutions at all levels.” This applies to both the public and private sectors, locally and globally.